Overcoming water scarcity and quality constraints: Domestic Water Supply, Hygine, and Sanitation - van Damme, Hans (International Food Policy Research Institute, 2001)
The Earth was home to 6 billion people in 2000: 1.1 billion of them lacked safe water and 2.4 billion lacked adequate sanitation. As a consequence, water- and sanitation-relation diseases are widespread. Nearly 250 million cases are reported every year, with more than 3 million deaths annually-about 10,000 a day.